The Influence of Leadership Style and Work Motivation on Employee Performance - Adi Suroso; Eka Ratna Damayanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research objective was to determine the effect of leadership style and work motivation on employee performance in the rendalprod warehouse department and the general department of PT. Pindad (Persero) Turen. Linear regression analysis from a sample of 76 employees with a significance level of 5% of the research results: (1). Leadership Style has a significant effect (0,291) on employee performance. (2). Work motivation has a significant effect (0,317) on employee performance. (3). The amount of influence of leadership style and work motivation simultaneously is 0,205. This shows that the leadership style and work motivation together have a significant effect on employee performance in the rendalprod, warehouse and general departments of PT. Pindad (Persero) Turen.